Effect of Rubberized Bitumen Blending Methods on Permanent Deformation of SMA Rubberized Asphalt Mixtures - Katman, H.Y.; Ibrahim, M.R.; Karim, M.R.; Koting, S.; Mashaan, N.S. (Hindawi Publishing Corporation, 2016)
This study aims at comparing the permanent deformation of Stone Mastic Asphalt (SMA) rubberized asphalt mixtures produced by the wet process. In this study, rubberized binders were prepared using two different blending methods, namely, continuous blend and terminal blend. To study the creep behaviour of control and rubberized asphalt mixtures, the dynamic creep test was performed using Universal Materials Testing Apparatus (UMATTA) at different temperatures and stress levels. Zhou three-stage creep model was utilized to evaluate the deformation characteristics of the mixtures. In all test conditions, the highest resistance to permanent deformation is showed by the rubberized mixtures produced with continuous blend binders. This study also reveals that the permanent deformation of rubberized mixtures cannot be predicted based on the characteristics of the rubberized binders.